The organization of the tadpole and adult alpha globin genes of Xenopus laevis. - Patient, R; Banville, D; Brewer, A; Elkington, J; Greaves, D; Lloyd, M; Williams, J (1982)
Adult erythrocytes of X. laevis contain six electrophoretically resolvable globin polypeptides while tadpole erythrocytes contain four polypeptides, none of which comigrates with an adult protein. We show that three of the adult proteins are alpha globin polypeptides (alpha 1, alpha 2, alpha 3) and three are beta globin polypeptides (beta 1, beta 2, beta 3). We find that a tadpole alpha globin gene (alpha T1) is linked to the major adult locus in the sequence 5'-alpha T1-alpha 1-beta 1-3' with 5.2 kb separating alpha T1 from alpha 1. Another tadpole alpha globin gene (alpha T2) is linked to the minor adult locus in the sequence 5'-alpha T2-alpha 2-beta 2-3' with 10.7 kb separating alpha T2 from alpha 2. These linkage relationships are consistent with the major and minor loci having arisen by tetraploidization but the different separation of larval and adult globin genes at the two loci indicates the occurrence of some additional chromosomal rearrangement. Two alternative models are presented.